KEMAMPUAN MENENTUKAN UNSUR INTRINSIK CERPEN “REMBULAN DI MATA IBU” KARYA ASMA NADIA SISWA KELAS XI SMA NEGERI 12 BULUKUMBA: The Ability to Determine the Intrinsic Elements of The Short Story “Rembulan di Mata Ibu” by Asma Nadia, A Student in Class XI at Sma Negeri 12 Bulukumba - Ervina Anugrah; Akmahl Hamsa; Aswati Asri (Study Program of Indonesian Language Education, Faculty of Languages and Literature, Universitas Negeri Makassar, 2026)
This research aims to describe the ability to determine the intrinsic elements of the short story Rembulan in the Eyes of Ibu Karya Asma Nadia, Class XI Student of SMA Negeri 12 Bulukumba. This research is a type of quantitative research. The data source was found from the results of class XI science students at SMA Negeri 12 Bulukumba. The research instrument used in this study was a multiple choice test regarding the intrinsic elements of the short stories read. The results of the study showed that the ability of class XI IPA 1 students of SMA Negeri 12 Bulukumba in determining the intrinsic elements of the short story 'Rembulan di Mata Ibu' by Asma Nadia was generally categorized as quite capable, with an average score of 72